About a Math Textbook for Engineering Students - Varga, Adrienn (International Journal of Engineering and Management Sciences, 2017)
What is the optimal amount of the theory in engineering mathematics education? How to be precise and effective at the same time? We present an attempt to answer these questions by a textbook containing higher level mathematics, especially calculus, for engineering students.